A Vibrational Spectral Maker for Probing the Hydrogen-Bonding Status of Protonated Asp and Glu Residues - Nie, Beining (Biophysical Society, 2005)
Hydrogen bonding is a fundamental element in protein structure and function. Breaking a single hydrogen bond may impair the stability of a protein. We report an infrared vibrational spectral marker for probing the hydrogen-bond number for buried, protonated Asp or Glu residues in proteins. Ab initio computational studies were performed on hydrogen-bonding interactions of a COOH group with a variety of side-chain model compounds of polar and charged amino acids in vacuum using density function theory. For hydrogen-bonding interactions with polar side-chain groups, our results show a strong correlation between the C=O stretching frequency and the hydrogen bond number of a COOH group: ∼1759–1776 cm(−1) for zero, ∼1733–1749 cm(−1) for one, and 1703–1710 cm(−1) for two hydrogen bonds. Experimental evidence for this correlation will be discussed. In addition, we show an approximate linear correlation between the C=O stretching frequency and the hydrogen-bond strength. We propose that a two-dimensional infrared spectroscopy, C=O stretching versus O-H stretching, may be employed to identify the specific type of hydrogen-bonding interaction. This vibrational spectral marker for hydrogen-bonding interaction is expected to enhance the power of time-resolved Fourier transform infrared spectroscopy for structural characterization of functionally important intermediates of proteins.